How many reptile and amphibian species are in Uganda, and why it matters for global biodiversity conservation - Hughes, Daniel F; Behangana, Mathias (PeerJ. Ltd, 2025)
Biodiversity is unevenly distributed across the globe. Regional differences in biodiversity impact conservation through the allocation of financial resources, development of infrastructure, and public attention. Such resources are often prioritized to areas that are in more need than others. However, reasons for deciding which locations are more deserving are derived from an accurate knowledge of the number and composition of species that occur in each region. Regional differences in biodiversity, however, can reflect differences in the source of information consulted, rather than bona fide differences between areas. As a result, conservation resources may not be directed to regions in proportion to their actual need, especially if there is no consensus among sources of information. Here, we compared major sources of information on species of reptiles and amphibians that occur in Uganda, Africa. We found that none of the sources agreed on the total number, nor composition, of species in the country, with estimates for amphibians ranging more widely than those for reptiles. Notably, sources with similar species richness differed in species composition, which had an impact on the number of threatened species in the country. These results for a conspicuous group of vertebrates suggest that lesser-known groups are also likely misrepresented in sources, especially in other underexplored regions of tropical Africa. We discuss the implications for biodiversity conservation that are derived from inaccurate species lists that are commonly used by agencies, scientists, and practitioners. We argue that more critical evaluations of biodiversity resources, in addition to greater capacity building for field programs, taxonomy, and museum collections, will be essential to ensure that resources are allocated to regions that need them the most.